PARADIGMA MAKNA FINAL DAN MENGIKAT PUTUSAN DEWAN KEHORMATAN PENYELENGGARA PEMILU - Ismail, Ismail; Hapsoro, Fakhris Lutfianto (Justitia et Pax, 2021)
In several cases of settlement of the State Administrative Court, the Panel of Judges annulled the Presidential Decree (beschikking) which followed up on a Decision of the Honorary Council of Election Organizers regarding the dishonorable dismissal of members of the General Election Commission. Basically, the decision of the Honorary Election Organizing Council is final and binding. With this practice in mind, this paper discusses how the paradigm is "final and binding" in the Decisions of the Honorary Election Organizing Council and what the consequences are for legal certainty. This paper uses a normative juridical approach. The results of this paper indicate that the "final and binding" nature of the DKPP Decision has a paradigm of meaning and creates uncertainty and disruption of legal order in the administration of elections and nullifies the essence of the existence of DKPP as an ethical judiciary institution that balances power (checks and balances).